The effectiveness of bidder remedies for enforcing the EC public procurement rules: a case study of the public works sector in the United Kingdom and Greece - Pachnou, Despina (2003)
The enforcement of EC procurement law relies heavily on legal action brought by aggrieved bidders for public contracts before the national courts. National remedies for bidders have been harmonised by two EC directives. The study considers the extent to which a system of bidder remedies is an effective mechanism for enforcing the procurement rules, through text-based research of the public sector procurement remedies and an empirical study in the construction sector, based on interviews with bidders, awarding authorities and procurement lawyers, in two Member States, Greece and the United Kingdom. The findings of the research indicate that remedies are not in principle incapable of assisting enforcement but that the use that is made of them and their capacity to enforce the law depend on their features, in terms, particularly, of legal costs as well as of the likelihood of a case being won at trial. Before this project was undertaken, there was no empirical research work on procurement remedies. It is hoped that this study will interest everyone involved in contracts awards (namely, firms, public bodies and lawyers) as well as scholars of EC law studying the national enforcement of EC rules, either in the area of procurement or in other areas regulated by EC law. It is also hoped that the findings of the studywill be of some use to policy and law makers, at European and national level.